Exploring Red, Green, and Blue Light‐Activated Degradation of Perovskite Films and Solar Cells for Near Space Applications. Issue 3 (23rd December 2019) - Xiao, Wei; Yang, Jianming; Xiong, Shaobing; Li, Danqin; Li, Yanqing; Tang, Jianxin; Duan, Chungang; Bao, Qinye
Abstract : Hybrid perovskite solar cells with a high specific power have great potential to become promising power sources mounted on spacecrafts in space applications. However, there is a lack of study on their photostability as light absorbers in those conditions. Herein, the stability of the perovskite films and solar cells under red, green, and blue (RGB) light illumination in medium vacuum that belongs to near space is explored. The perovskite active layers exhibit different degradations from morphological, chemical, and structural points of view. This is attributed to the strong coupling between photoexcited carriers and the crystal lattice and the diversity of RGB light absorption in the perovskite films. Device characterizations reveal that the efficiency loss of perovskite solar cells results from not only perovskite degradation, but also the photoexcited carriers reducing the energy barrier of ion migration and accelerating the migration to generate more deep‐level trap defects. Moreover, comparative devices suggest that the well encapsulation can weaken the effect of vacuum on stability. Abstract : The photostability of perovskite films and solar cells under red, green, and blue (RGB) light illumination in medium vacuum that belongs to near space is systemically investigated as a promising power source mounted on spacecrafts. It is found that RGB light induces different degradations of perovskites from morphological, chemical, structural, and device performance points of view.